2019
DOI: 10.4103/eus.eus_59_18
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of proton pump inhibitor use reduces the number of endoscopic procedures required for resolution of walled-off pancreatic necrosis

Abstract: Background and Objectives: Endoscopic drainage/debridement of symptomatic walled off necrosis (WON) using lumen-apposing metal stents (LAMS) is both safe and effective. While endoscopic management of WON is the standard approach to treatment, the ideal concomitant medical therapy remains unclear. The purpose of this study was to further elucidate the effect of proton pump inhibitor (PPIs) therapy on the technical and clinical success of endoscopic treatment of WON. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Although PPIs were found to be associated with a decreased risk of PP, they were not associated with the occurrence of WON, IPN, and total hospital stay or mortality in our study. In previous studies, PPIs have been reported to increase the risk of necrosis and infection (Min et al, 2019;Powers et al, 2019). Drainage is the main option for pancreatic necrosis, but a recent study revealed that reducing PPIs use can decrease the number of endoscopic procedures for treating WON (Powers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PPIs were found to be associated with a decreased risk of PP, they were not associated with the occurrence of WON, IPN, and total hospital stay or mortality in our study. In previous studies, PPIs have been reported to increase the risk of necrosis and infection (Min et al, 2019;Powers et al, 2019). Drainage is the main option for pancreatic necrosis, but a recent study revealed that reducing PPIs use can decrease the number of endoscopic procedures for treating WON (Powers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, PPIs have been reported to increase the risk of necrosis and infection (Min et al, 2019;Powers et al, 2019). Drainage is the main option for pancreatic necrosis, but a recent study revealed that reducing PPIs use can decrease the number of endoscopic procedures for treating WON (Powers et al, 2019). Peripancreatic infection can be caused by intestinal bacteria translocation after compromised gastrointestinal barrier function (Demcsak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aggressive lavage with large-volume warmed antibiotic solution has also been reported as an efficient alternative to saline irrigation, and reduced rates of adverse events and mortality have been noted in previous studies[ 91 ]. In addition, cessation of PPIs, local infusion of antibiotics, maximal fragmentation of necrotic tissue, and disruption of internal septate structures during the first necrosectomy can also improve drainage and reduce debridements[ 91 - 93 ].…”
Section: Endoscopic Transluminal Necrosectomymentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) and other antacids are not recommended after a cystenterostomy because it is thought that the acidity of the stomach assists in the elimination of the necrotic tissue. Discontinuing PPIs has been shown to reduce the number of endoscopic procedures required 25. Antibiotics are only indicated in patients with infected necrosis and are not recommended for patients with necrotizing pancreatitis without infection.…”
Section: Managementmentioning
confidence: 99%